High-resolution virtual try-on with garment extraction using generative adversarial networks - Charters, Daniel J (Department of Statistical Sciences, 2025)
Image-based virtual try-on aims to depict an individual wearing a garment not originally worn by them. While existing literature predominantly focuses on garments from standalone images, this research addresses the use of images where the garment is already being worn by another individual. The study bridges a notable gap as most current systems are tailored for standalone garment images. The proposed system, given a pair of high-resolution images, extracts the garment from one, refines it using context-aware image inpainting, and subsequently transfers it onto the second image's subject. The methodology incorporates various off-the-shelf models, notably Part Grouping Network (PGN), Densepose, and OpenPose for pre-processing. A state-of-the-art context-aware inpainting model refines the garments, and the final synthesis leverages the HR-VITON architecture, producing images at a resolution of 768 × 1024. Distinctively, our model processes both standalone and garment-on-person images. Evaluating the models involves testing on 2 032 high-resolution images under both paired and unpaired conditions. Metrics such as RMSE, Peak Signal-to-Noise Ratio (PSNR), Learned Perceptual Image Patch Similarity (LPIPS), Structural Similarity (SSIM), Inception Score (IS), Fréchet Inception Distance (FID), and Kernel Inception Distance (KID) assessed the model's prowess. Benchmarked against HR-VITON, ACGPN, and CP-VTON, our model slightly trailed HR-VITON but notably surpassed ACGPN and CP-VTON. In realistic, unpaired conditions, the model achieved an IS of 3.152, an FID of 15.3, and a KID of 0.0063. This is compared to an IS of 3.398, an FID of 11.93, and a KID of 0.0034 achieved by HR-VITON on the same data. ACGPN has an FID of 43.29, and a KID of 0.0373, while CP-VTON has an FID of 43.28, while it has a KID of 0.0376. IS is not measured for both ACGPN and CP-VTON. An ablation study underscored the importance of context-aware inpainting in our network. The findings highlight the model's ability to generate convincing, high-resolution virtual try-on images from garment-on-person extractions, addressing a prevalent gap in the literature and offering tangible applications in high-resolution virtual try-on image generation.